2018
DOI: 10.1177/1471301218800641
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and understanding of dementia in South Asians: A synthesis of qualitative evidence

Abstract: Background Despite a growing elderly South Asian population, little is known about the experience of diagnosis and care for those living with dementia. There have been a number of individual qualitative studies exploring the experiences of South Asian people living with dementia and their carers across different contexts. There has also been a growing interest in synthesizing qualitative research to systematically integrate qualitative evidence from multiple studies to tell us more about a topic at a more abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 48 publications
7
38
2
Order By: Relevance
“…This study is the first to consider in more detail the organization of family dementia care in Turkish, Pakistani, and Arabic speaking minority ethnic families in Denmark. As in previous studies in minority ethnic communities in Europe (Baghirathan et al, 2018;Berdai Chaouni & De Donder, 2018;Hossain et al, 2018;Naess & Moen, 2015;Parveen et al, 2017;Sagbakken, Spilker, & Ingebretsen, 2018;Sagbakken, Spilker, & Nielsen, 2018;van Wezel et al, 2016), we found a preference for keeping dementia care within the family with limited support from formal care services but more details about how this was managed by the families.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study is the first to consider in more detail the organization of family dementia care in Turkish, Pakistani, and Arabic speaking minority ethnic families in Denmark. As in previous studies in minority ethnic communities in Europe (Baghirathan et al, 2018;Berdai Chaouni & De Donder, 2018;Hossain et al, 2018;Naess & Moen, 2015;Parveen et al, 2017;Sagbakken, Spilker, & Ingebretsen, 2018;Sagbakken, Spilker, & Nielsen, 2018;van Wezel et al, 2016), we found a preference for keeping dementia care within the family with limited support from formal care services but more details about how this was managed by the families.…”
Section: Discussionsupporting
confidence: 82%
“…Although different care models were identified, rotational 24-hour care-either by having the person with dementia live with different family members or by having different family members take turns to move in with the person with dementiaemerged as a common alternative to formal care. As in other research in Turkish, Pakistani, and Arabic speaking communities (Berdai Chaouni & De Donder, 2018;Hossain et al, 2018;van Wezel et al, 2016), it was evident that children of the person with dementia were central in these care arrangements. However, previous research has not focused on organization of shared family care, despite this care model has been considered when discussing dementia care in Turkish, Pakistani, and Arabic speaking minority ethnic communities (Boughtwood et al, 2011;Lawrence et al, 2008;Sagbakken, Spilker, & Ingebretsen, 2018).…”
Section: Discussionsupporting
confidence: 73%
“…Despite an increasing number of older people from the Bangladeshi community in England, little or no specific research has been carried out on their understanding and management of dementia [13,14]. As a result of the lack of primary research in this area, there was a need to conduct a primary qualitative study among the Bangladeshi community and to provide a coherent critical description and interpretation of their knowledge about, experiences with, and perceptions of dementia.…”
Section: Rationalementioning
confidence: 99%
“…Dementia can be debilitating not only for the older person with dementia, but for family members as well [12]. However, there is little discussion about the British South Asian community and dementia in the literature, and there are no exact figures regarding the prevalence of dementia in Black, Asian, and Minority Ethnic (BAME) groups in the UK [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A recent qualitative systematic review indicates that there is no word for "carer" in South Asian languages [1]. Traditionally, caring responsibility in the South Asian community falls to the younger family members in the household, especially daughters-in-law or unmarried daughters.…”
Section: Introductionmentioning
confidence: 99%